Method for preparing a glass convenient for trimming, a glass thus obtained, and method for trimming such a glass - CONTE DOMINIQUE; LACAN PASCALE (2016)
A method that allows trimming glass comprising a hydrophobic and/or oil-repellent surface coating, where a temporary protective layer is coated on the surface of said glass and the temporary protective layer imparts to the glass a surface energy of at least 15 mJ/m2.